Judaism and the Euthyphro Dilemma: Towards A New Approach - Sztuden, Alex (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2018)
This article attempts to utilize representative talmudic source-material that bears on the Euthyphro dilemma, and more widely, that discusses the central role of human agency in the foundations of Jewish law, in order to sketch a modified version of divine command theory (DCT), under which both horns of the traditional dilemma are grasped. That is, the proposed modified DCT, based on talmudic sources, is one in which God is properly placed at the foundation of the moral law, while simultaneously providing a central role for human moral reasoning. The first main section presents and evaluates Michael Harris’s pioneering analysis of the Euthyphro dilemma in classical Jewish sources, while the second main section attempts to sketch a new approach out of classical Jewish sources.